Monitoring Aktifitas Siswa Menggunakan RFID Terintegran Web - Husna, Himayatul; Budiarso, Zuly (STIKOM Tunas Bangsa Pematangsiantar, 2024)
Student activity at school is an important factor in ensuring security, order and operational efficiency. Student attendance at school is an important element in managing student attendance and ensuring a safe school environment. The proposed system uses RFID technology to simplify the process of recording student attendance automatically, efficiently and accurately. This system consists of two main components, namely RFID readers installed at school entrances and a web-based server. When students pass through a door equipped with an RFID reader, their RFID card will be read, and the student's entry or exit information will be recorded in a database connected to the web platform. On the web platform, users can view student activity reports, access historical data.